In situ northern mid-latitude observations of ClO, O3, and BrO in the wintertime lower stratosphere - Brune, W. H.; Toohey, D. W.; Anderson, J. G.; Starr, W. L.; Vedder, J. F.; Danielsen, E. F. (1988)
In order to test photochemical theories linking chlorofluorocarbon derivatives to O3 depletion at high latitudes in the springtime, several related atmospheric species, including O3, ClO, and BrO were measured in the lower stratosphere. The flight path extended to the center of the polar jet associated with but outside of the Arctic vortex, in which the abundance of O3 was twice its midlatitude value, whereas BrO levels were five parts per trillion (pptv) by volume between 18 and 21 km, and 2.4 pptv below that altitude. The ClO mixing ratio was as much as 65 pptv at 60 N latitude at an altitude of 20 km, and was enhanced over midlatitude values by a factor of three to five at altitudes above 18 km and by as much as a factor of 40 at altitudes below 17 km. Levels of ClO and O3 were highly correlated on all measured distance scales, and both showed an abrupt change in character at 54 N latitude. The ClO abundance north of 54 N was probably caused by low NO2 levels in the flight path.